2013
DOI: 10.1590/s1516-14392013005000091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperatures and strain rates on the average size of grains refined by dynamic recrystallization for as-extruded 42CrMo steel

Abstract: In order to study the dynamic recrystallization (DRX) behavior of as-extruded 42CrMo highstrength steel, a series of isothermal upsetting experiments were carried out in a temperature range of 1123~1348 K and a strain rate range of 0.01~10 s -1 on Gleeble 1500. It was found that DRX softening is more recognizable at higher temperatures and lower strain rates, and stress level increases with increasing strain rate and decreasing deformation temperature. The types of flow stress evolution were distinguished by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…For a fixed temperature, as strain rate increases, recrystallized grains have not enough growth time, and stored energy (i.e., high nucleation rate) increases, thus more refined grains will be achieved. Similar results were found by Guo-zheng et al [29] processing 42CrMo Steel and Fatemi-Varzaneh et al [30] processing AZ31 alloy. Grain size measurements were performed according to ASTM E112-12 [31].…”
Section: Dynamic Recrystallized Grain Sizesupporting
confidence: 88%
“…For a fixed temperature, as strain rate increases, recrystallized grains have not enough growth time, and stored energy (i.e., high nucleation rate) increases, thus more refined grains will be achieved. Similar results were found by Guo-zheng et al [29] processing 42CrMo Steel and Fatemi-Varzaneh et al [30] processing AZ31 alloy. Grain size measurements were performed according to ASTM E112-12 [31].…”
Section: Dynamic Recrystallized Grain Sizesupporting
confidence: 88%
“…In this stage, the dislocation density increases as the strain enhances, promoting the subgrain formation [16]. It has also been reported that DRX initiates before reaching the stress peak, but it cannot be said that it is initiated in austenite or ferrite [17][18][19].…”
Section: The Region Where Values Of ''Wh Rate'' Are Positivementioning
confidence: 99%
“…and WH[16]. No indication of steady-state flow is observed as WHR value does not reach zero, which corresponds to the onset of steady-state flow (balance between…”
mentioning
confidence: 97%
“…The effects of temperature and strain rate can be expressed in terms of the second-order function of the Zener-Hollomon parameter, Z, in an exponent-type function of temperature and strain rate, as follows [29]:…”
Section: Summary: 6xxx Aluminum Alloys For a High-speed Extrusionmentioning
confidence: 99%